Neuron-Derived Estrogen Regulates Synaptic Plasticity and Memory - Lu, Yujiao (J Neurosci, 2019)
17β-estradiol (E2) is produced from androgens via the action of the enzyme aromatase. E2 is known to be made in neurons in the brain, but its precise functions in the brain are unclear. Here, we used a forebrain-neuron-specific aromatase knock-out (FBN-ARO-KO) mouse model to deplete neuron-derived E2 in the forebrain of mice and thereby elucidate its functions. FBN-ARO-KO mice showed a 70–80% decrease in aromatase and forebrain E2 levels compared with FLOX controls. Male and female FBN-ARO-KO mice exhibited significant deficits in forebrain spine and synaptic density, as well as hippocampal-dependent spatial reference memory, recognition memory, and contextual fear memory, but had normal locomotor function and anxiety levels. Reinstating forebrain E2 levels via exogenous in vivo E2 administration was able to rescue both the molecular and behavioral defects in FBN-ARO-KO mice. Furthermore, in vitro studies using FBN-ARO-KO hippocampal slices revealed that, whereas induction of long-term potentiation (LTP) was normal, the amplitude was significantly decreased. Intriguingly, the LTP defect could be fully rescued by acute E2 treatment in vitro. Mechanistic studies revealed that FBN-ARO-KO mice had compromised rapid kinase (AKT, ERK) and CREB-BDNF signaling in the hippocampus and cerebral cortex. In addition, acute E2 rescue of LTP in hippocampal FBN-ARO-KO slices could be blocked by administration of a MEK/ERK inhibitor, further suggesting a key role for rapid ERK signaling in neuronal E2 effects. In conclusion, the findings provide evidence of a critical role for neuron-derived E2 in regulating synaptic plasticity and cognitive function in the male and female brain. SIGNIFICANCE STATEMENT The steroid hormone 17β-estradiol (E2) is well known to be produced in the ovaries in females. Intriguingly, forebrain neurons also express aromatase, the E2 biosynthetic enzyme, but the precise functions of neuron-derived E2 is unclear. Using a novel forebrain-neuron-specific aromatase knock-out mouse model to deplete neuron-derived E2, the current study provides direct genetic evidence of a critical role for neuron-derived E2 in the regulation of rapid AKT-ERK and CREB-BDNF signaling in the mouse forebrain and demonstrates that neuron-derived E2 is essential for normal expression of LTP, synaptic plasticity, and cognitive function in both the male and female brain. These findings suggest that neuron-derived E2 functions as a novel neuromodulator in the forebrain to control synaptic plasticity and cognitive function.